Reisbauökosysteme mit künstlicher Bewässerung und mit pluvialer Wasserzufuhr: Java und analoge Typen im übrigen Südostasien - Uhlig, Harald (ERDKUNDE, 1984)
SE Asia's most intensively, anthraquic-manipulated ecotopes are the irrigated terraces and plains, most notably between the volcanoes of Java, Bali, parts of the Philippines and other monsoon tropical islands. Heavy population pessure demands double-cropping, transplanting, increasing multiple crop rotations, puddling of near-artificial rice-soils and a long tradition of organized irrigation societies. Irrigation is subdivided according to geoecological sites: by (improved) natural flooding; riverfed canal-irrigation of lowland plains; slope-canal irrigation of terrace-systems and valleys; lift-irrigation (from rivers or phreatic) and retention (impounding) of rainfall. The diagram: Model C (supplement I) aims to represent all types; references are made also to A (Mainland SE Asia) and B (Humid Tropical Islands) (ERDKUNDE 37,4,1983; supplements VIII, LX). A model of a 0.6 ha tenant-farm (fig. 1) is compared to that of a 6 ha owner-farm in Thailand's natural flooding areas (ERDKUNDE 37,4; fig. 4), showing similar yields, but heavy input of labour in Java to compensate for the smaller size and less favourable socio economic conditions. Natural and socio-cultural reasons for the much differentiated, regional distribution of wet-rice terraces in SE Asia and ecological arguments for the early diffusion of wet- and dryland-rice in Indonesia are discussed. Pluvial rice-cultivation includesrice on impounded rainfall (rain-sawah, by ponding) - a quite distinct type within the ambivalent group of rainfed-rice, practically transitional from irrigated to dryland-rice, occupying 1/4-1/5 of SE Asia's ricelands. Dry (upland-)rice appears in three ecosystems: shifting cultivation (padi ladang), by dibble, swiddening and in land-rot2X\on\ dryland-rice on permanent arable land (padi gogo - in crop rotation) on openfields, or intercropped under tree-cultivation and other annuals. The latter is also practiced by dibble, but in permanent cultivation in part on open terraces. Mixed dryland tree (kebun) and field-crops (including dryland-rice - tegalan) have replaced large tracts of former shifting cultivation. Geoecological and physiological aspects, and strong natural and human adaptive selection, indicate an origin of rice-cultivation in the seasonally flooded monsoon-tropical areas, whereas dryland-rice was gradually branched off on dryer (still sufficiently moist) ground more recently. To explain the wide range of the ecological continuum of rice cultivation systems in SE Asia is the purpose of these papers and their pictorial models (A-C). Table 1 summarizes the short definitions and terms of the various rice-irrigation types and sites.